Numerical investigation on reduced moment resistance and increased reinforcement spacing in reinforced concrete wall subjected to blast load - M. A., Seman; Sharifah Maszura, Syed Mohsin; A.M.A., Zaidi; Z. M., Jaini (Penerbit UTHM, 2022)
Numerical investigation becomes a highly demanding tool for the best design in engineering. With one validated numerical result available, further investigation is possible to conduct. Especially, for the expensive and limited access for civilian to conduct the test like a blast experiment. With the capability of Arbitrary Lagrange Euler (ALE) solver coupling approach between structure and air in AUTODYN, a detail three-dimensional assessment for RC wall on reduced moment resistance and increased reinforcement spacing are conducted. The RC wall has a crosssectional dimension of 1829 mm x 1219 mm with wall thickness of 305 mm thickness of strip footing. It is subjected to 13.61 kg Trinitrotoluene (TNT) explosive at 1.21 m standoff distance from the centre. The numerical blast impact on RC wall indicated, although the horizontal and vertical flexural reinforcements are reduced from one of the simulated RC walls, it is capable of demonstrating an equivalent strength to the RC wall tested in the experiment.